ANTIOXIDANT AND ANTI-INFLAMMATORY EFFECT OF Morinda citrifolia: A META-ANALYSIS AND SYSTEMATIC REVIEW - Ervina Vashti; Bernard Christoper Fernando Oen; Eric Ricardo Yonatan; Venna Bella Sabatina; Sherlyn Sean; Elisabeth Rukmini (Universitas Pakuan, 2022)
Morinda citrifolia (noni) is a tropical plant from the Rubiaceae family, which contains various active components that have several functions in medical fields that can act as an antioxidant and anti-inflammatory. To assess both effects, we conducted a systematic review and meta-analysis, with the PRISMA statement guidelines, to discuss the efficacy of Morinda citrifolia as an antioxidant and anti-inflammatory. The literature search was performed by searching through 12 databases: Sage Journals, ScienceDirect, Garuda, ProQuest, PubMed, Google Scholar, Web of Science, Taylor and Francis, Wiley Online Library, Cochrane Library, EBSCO, and SINTA from 2000 to 2020. From 4.605 identified record journals, we found six journals which were included in our study analysis. Our analysis showed that Morinda citrifolia has a moderate positive effect as antioxidant and anti-inflammatory agents, with an overall effect size of correlation 0.46 (CI 95% was 0.37-0.54). This study proves the potential of Morinda citrifolia as an alternative herbal medicine. Future research and studies are expected on Morinda citrifolia to investigate its further potential.